2014
DOI: 10.1093/jac/dku351
|View full text |Cite
|
Sign up to set email alerts
|

β-Lactam/β-lactamase inhibitors versus carbapenems for the treatment of sepsis: systematic review and meta-analysis of randomized controlled trials

Abstract: No differences in efficacy between BL/BLIs and carbapenems exist in RCTs including patient populations with a certain, albeit unknown, rate of ESBL-positive bacteria causing infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 38 publications
1
34
1
1
Order By: Relevance
“…BLBLIs have been shown to be as effective as carbapenems for the treatment of diverse severe infections in randomized trials (21). The reasons for raising doubts about the efficacy of BLBLIs in the treatment of severe infections caused by ESBL-E include the fol- lowing.…”
Section: Discussionmentioning
confidence: 99%
“…BLBLIs have been shown to be as effective as carbapenems for the treatment of diverse severe infections in randomized trials (21). The reasons for raising doubts about the efficacy of BLBLIs in the treatment of severe infections caused by ESBL-E include the fol- lowing.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, given the low number of patients receiving targeted BLBLI therapy, we cannot draw any firm conclusion. To date, the published data on the use of BLBLIs for the treatment of infections caused by ESBL-GNB are conflicting and mainly refer to nonimmunocompromised patients (13)(14)(15)(16)(17)(18)(19)(20)(21). Our study was the first to assess the usefulness of BLBLIs for the treatment of ESBL-BSI in a severely immunosuppressed cohort of hematological patients with neutropenia.…”
mentioning
confidence: 99%
“…This is particularly worrisome in a scenario in which carbapenem-resistant Enterobacteriaceae (CRE) are spreading rapidly and are adversely compromising patients' outcomes (7)(8)(9)(10)(11)(12). While recent investigations have suggested that ␤-lactam/␤-lactamase inhibitors (BLBLIs) may be reliable options for the treatment of BSI due to ESBL-producing Gram-negative bacilli (ESBL-GNB), especially in nonimmunocompromised patients (13)(14)(15)(16)(17)(18)(19), other studies have found contrasting data (20,21). To date, the efficacy of BLBLIs for the treatment of BSI due to ESBL-GNB in high-risk hematological patients has not been established.…”
mentioning
confidence: 99%
“…Although some studies have proposed a combination of β‐lactam/β‐lactamase inhibitors as an alternative to carbapenems for treating these resistant strains in the general population , the usefulness of this approach for the treatment of BSI in SOT recipients has not been conclusively demonstrated. The INCREMENT‐SOT project, currently in progress, should shed light on this issue .…”
Section: Discussionmentioning
confidence: 99%